Constraints on the origin of cosmic rays from large scale anisotropy searches in data of the Pierre Auger Observatory - De Almeida, Rogerio M. (2013)
We update a search for large scale anisotropies in the distribution of arrival directions of cosmicrays detected above 1018 eV at the Pierre Auger Observatory as a function of both the right ascension and thedeclination. Within the systematic uncertainties, no significant deviation from isotropy is revealed. Upper limits ondipole and quadrupole amplitudes are updated under the hypothesis that any cosmic ray anisotropy is dominatedby such moments in this energy range. These upper limits provide constraints on the production of cosmic raysabove 1018 eV, since they allow us to challenge an origin from stationary galactic sources densely distributed inthe galactic disk and emitting predominantly light particles in all directions.